Modernization in Wing Kardjo’s ‘Pasar’: Intertextual resonances with Baudelaire and Rimbaud’s poems - Nurnaningrum, Sri; Umaya, Nazla Maharani; Harjito (Universitas Muhammadiyah Malang, 2024)
This research aims to analyzehow the poem “Pasar” in “Fragment Malam –Setumpuk Soneta” by Wing Kardjo reflects and critiques urbanizationand how its intertextual connections with Charles Baudelaire’s “Le Cygne II” in “Les Fleurs du Mal” and Arthur Rimbaud’s “Métropolitain” in “Illuminations” serve as hypograms. Despite Kardjo's significance in modern Indonesian poetry, no studies have explored his poems' engagement with French literature. Through intertextual analysis using Kristeva's framework and comparative studies, it wasfound that Kardjo's poem and French poets share the same themes of modernizationand its impacts. The findings demonstrate that Kardjo’s “Pasar” resonates with Baudelaire's and Rimbaud's poems andrecontextualizesthem within the Indonesian socio-cultural landscape ofthe New Order Era. Theanalysis reveals three primary intertextual themes shared with both Baudelaire's and Rimbaud’s poems: (1) urban transformation, (2) critique of modernization, and (3) nostalgia and melancholy for the past. The themes like (1) loss and displacementand (2) alienation are drawn from Baudelaire’s work,while the theme of industrializationechoes Rimbaud’s poetry. This intertextual study in a transcultural context enhances the understanding of modernity in Kardjo’s work anddemonstrates the French influences that shaped Indonesian poetry.